MKI-1, a Novel Small-Molecule Inhibitor of MASTL, Exerts Antitumor and Radiosensitizer Activities Through PP2A Activation in Breast Cancer - Kim, Ah-Young; Yoon, Yi Na; Leem, Jiyeon; Lee, Jee-Young; Jung, Kwan-Young; Kang, Minsung; Ahn, Jiyeon; Hwang, Sang-Gu; Oh, Jeong Su; Kim, Jae-Sung (Frontiers in Oncology, 2020)
Although MASTL (microtubule-associated serine/threonine kinase-like) is an attractive target for anticancer treatment, MASTL inhibitors with antitumor activity have not yet been reported. In this study, we have presented a novel MASTL inhibitor, MKI-1, identified through in silico screening and in vitro analysis. Our data revealed that MKI-1 exerted antitumor and radiosensitizer activities in in vitro and in vivo models of breast cancer. The mechanism of action of MKI-1 occurred through an increase in PP2A activity, which subsequently decreased the c-Myc protein content in breast cancer cells. Moreover, the activity of MKI-1 in the regulation of MASTL-PP2A was validated in a mouse oocyte model. Our results have demonstrated a new small-molecule inhibitor of MASTL, MKI-1, which exerts antitumor and radiosensitizer activities through PP2A activation in breast cancer in vitro and in vivo.